COMPARISON OF 10 SORGHUM (Sorghum bicolor L) GENOTYPES UNDER VARIOUS WATER STRESS REGIMES - S. Saddam; A. Bibi1; H. A. Sadaqat; B. F. Usman (Journal of Animal and Plant Sciences, 2014)
Ten different accessions of sorghum (Sorghum bicolor L.) were evaluated for their ability to drought tolerance at seedling stage. Three water stress levels (50%, 75%, and 100%) were applied under controlled conditions. After twenty eight days of seedling emergence, data were recorded for seedling and physiological traits as shoot length (SL), root length (RL), shoot fresh weight (SFW), shoot dry weight (SDW), root fresh weight (RFW), root dry weight (RDW), leaf area (LA), relative water contents (RWC), residual transpiration (RT), chlorophyll ‘a’ and Chlorophyll ‘b’ under control as well as two water stressed conditions. Significant differences were observed among the genotypes, treatments and their interactions for evaluated plant traits suggesting a great amount of variability for water stress tolerance in sorghum. However, shoot related traits were the most sensitive against the water stress. Stress tolerance indices of SL, RL, SDW, RWC, SFW and LA, RT, RFW, RDW, Chl ‘a’ Chl ‘b’ was 84%, 73 %, 61%, 59%, 56%, 43%, 43% 33%, 32%, 16% and 15%, respectively. Soot length (84%) was the highest towards drought susceptible, indicating shoot length was most affected by water stress among all the seedling traits. The most promising drought tolerant accession (NO.1749) and drought susceptible F-2007 and F-2008) were screened.
Keywords: Sorghum bicolor L.; Seedling traits; Physiological traits; Water stress